2021
DOI: 10.5194/aab-64-335-2021
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose can effectively protect sheep epididymis epithelial cells from oxidative stress

Abstract: Abstract. Trehalose, a naturally nontoxic disaccharide that does not exist in mammals, stabilizes cell membrane integrity under oxidative stress conditions, the mechanism of which is still unclear. Here, we analyzed the effects of trehalose on sheep epididymis epithelial cell (EEC) proliferation and its possible mechanisms. To study the effect of trehalose on EECs, EECs were isolated from testes of 12-month-old sheep; cell counting kit-8 (CCK-8) was used to measure the growth of the cells. Cell proliferation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been reported that the level of TAS in 1st week of postpartum in dairy cows decreases compared to the prenatal period, but increases in the following weeks, which is an advantage for fertility (Elshahawy 2017, Luan et al 2021). In the present study, it was determined that the offspring yield was high in goats with high TAS levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the level of TAS in 1st week of postpartum in dairy cows decreases compared to the prenatal period, but increases in the following weeks, which is an advantage for fertility (Elshahawy 2017, Luan et al 2021). In the present study, it was determined that the offspring yield was high in goats with high TAS levels.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of oxidative stress in epididymal epididymal cells in goats, miR-542-3p mRNA can downregulate the expression of GPX5, thereby aggravating oxidative damage in epididymal epididymal cells (Yang et al, 2022). In the study of the protective effect of trehalose on oxidative stress damage in sheep epididymal epididymal cells, it was again found that the upregulation of GPX5 plays a key role (Luan et al, 2021). It can be seen that GPX5 is essential in regulating oxidative stress damage in the epididymis and protecting sperm maturation, which is of great significance in maintaining the reproductive ability of mammals.…”
Section: Gpx5mentioning
confidence: 99%